Implementation of Akhlakul Karimah Values in Aqidah Akhlak Learning at MTs Negeri 12 Indramayu - Romyati; Didik Himmawan (Quality : Journal Of Education, Arabic And Islamic Studies, 2025)
The purpose of this study was to determine the values ​​of Akhlakul Karimah of students at MTs Negeri 12 Indramayu by Akidah Akhlak teachers through implementation in teaching and learning activities and outside teaching and learning activities. The data collection for this study used qualitative descriptive using the analysis study method through observation and documentation and literature studies were also the sources. This study also focused on subjects, students and teachers. The results of the discussion of this study show that the morals of students in the current era such as being untidy, skipping school during class hours and playing with cellphones are problems that must be improved by implementing Akhlakul Karimah values ​​such as instilling good faith, fairness and honesty, discipline, politeness and courtesy, mutual respect and appreciation, responsible and trusted, obedient and helpful, patient and positive thinking and of course encouraged by routine activities at the school, namely, Duha prayer, tilawah or reading the Qur'an, sholawat and Dhuhur prayer in congregation.